DOI: 10.31274/rtd-180813-13496
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Brucella abortus catalase as a defensive mechanism against oxidative stress

Abstract: Stinictiiral components of Brucella Pathogenesis of Brucella infection Oxidative stress in phagocytes Bacterial defensive mechanisms Catalase and superoxide dismutase Transcription factors of the LysR family 10 Rationale for this study References CHAPTER n. BRUCELLA ABORTUS PERIPLASMIC CATALASE IS REGULATED BY EXTERNAL HYDROGEN PEROXIDE 21 ABSTRACT INTRODUCTION 22 MATERIALS AND METHODS 24 Bacterial strains and medium 24 Construction of the deletion plasmid 24 Transformation of Brucella abortus 25 Halo assay (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The procedure followed that given in Current Protocols in Molecular Biology (2) modified for Brucella (10). In this assay, a pronounced gel shift was observed in the presence of Brucella soluble extract (data not shown).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure followed that given in Current Protocols in Molecular Biology (2) modified for Brucella (10). In this assay, a pronounced gel shift was observed in the presence of Brucella soluble extract (data not shown).…”
mentioning
confidence: 99%
“…Brucella abortus has a single hydroperoxidase, a true catalase, which is expressed in the periplasm (17). In previous studies (10,11), it was shown that Brucella catalase is regulated at the transcriptional level.…”
mentioning
confidence: 99%
See 1 more Smart Citation